Hydrolysis Of Waste Cooking Oil By Free Candida Rugosa Lipase - Andyappan, A Helan R (Universiti Sains Malaysia, 2022)
The removal of oil and grease from the wastewater treatment is a challenging issue when involving physical and chemical method due to the usage of hazardous chemical and having environmental problems. Thus, lipase is a proven novel method to remove or degrade lipid content in water system as it has a potential acting as biocatalyst. Waste cooking oil was chosen as the substrate for this study because Malaysia produces a large amount of it and because disposing of it has become a major environmental problem. Enzymatic assay of free lipase activity has been performed and the catalytic activity was 970.0 U/mg enzyme. Effect of reaction of time, temperature, water content, and enzyme loading on the hydrolysis process were investigated. The optimum reaction time for the hydrolysis process is 120 minutes It was observed that variables had a significant impact on the hydrolysis process. The hydrolysis process achieved the highest yield of fatty acids at the temperature of 45oC, buffer volume to oil volume ratio of 4:1, pH of 7, agitation speed of 140 rpm and enzyme concentration of 0.025 (w/v) %. Under these conditions, it was found that nearly 41.7% ± 0.253 of the free fatty acid conversion.